Expectation vs. Reality: Attitudes Towards a Socially Assistive Robot in Cardiac Rehabilitation - Casas, Jonathan A.; Céspedes, Nathalia; Cifuentes, Carlos A.; Gutierrez, Luisa F.; Rincón Roncancio, Mónica; Múnera, Marcela (MDPI (Multidisciplinary Digital Publishing Institute), 2019)
Currently, Social Assistive Robotics (SAR) is widely explored in different areas and scenarios. In cardiac rehabilitation, SAR has been recently implemented as a tool to improve the quality of the procedures and support patients to increase their performance. Ace cardiac rehabilitation Comprises numerous sessions, such systems must guarantee to be effective in the long term. Therefore, to achieve this goal, it is important to understand how users, specifically patients and clinicians who Mostly know the needs and the therapy environment, perceive this technology. In this context, This paper presents the assessment of the attitudes towards a social robot in order to evaluate the expectation of potential new users, and perception of users who interacted with the social robot during a period of 18 weeks performing cardiac rehabilitation. A total of 43 participants (28 patients and 15 clinicians) were included in the study, and acceptance and perception factors were evaluated through a modified UTAUT questionnaire model and open discussion sessions. Results show that 75% of patients have positive thoughts regarding the usefulness, utility, safety, and trust perceived of a social robot, and 80% of clinicians consider that the robot is a useful tool for cardiac rehabilitation. Similarly, a more positive perception was noticed after the users interacted with the robot. Furthermore, this perception study allows the enhancement of the social model of interaction in the future, aiming to provide a more natural interaction through personalized features, increasing social abilities and engagement of the users during the therapy.

Actualmente, la Robótica de Asistencia Social (SAR) es ampliamente explorada en diferentes áreas y escenarios. En rehabilitación cardíaca, el SAR se ha implementado recientemente como una herramienta para mejorar la calidad de los procedimientos y apoyar a los pacientes para aumentar su desempeño. Rehabilitación cardiaca as Consta de numerosas sesiones, dichos sistemas deben garantizar su eficacia a largo plazo. Por lo tanto, Para lograr este objetivo, es importante comprender cómo los usuarios, específicamente los pacientes y los médicos que Principalmente conoce las necesidades y el entorno de la terapia, percibe esta tecnología. En este contexto, Este artículo presenta la evaluación de las actitudes hacia un robot social con el fin de evaluar la expectativa de nuevos usuarios potenciales y la percepción de los usuarios que interactuaron con las redes sociales. robot durante un periodo de 18 semanas realizando rehabilitación cardíaca. Un total de 43 participantes (28 pacientes y 15 médicos) fueron incluidos en el estudio, y los factores de aceptación y percepción fueron evaluado a través de un modelo de cuestionario UTAUT modificado y sesiones de discusión abierta. Resultados muestran que el 75% de los pacientes tienen pensamientos positivos respecto a la utilidad, utilidad, seguridad y confianza percibido de un robot social, y el 80% de los médicos consideran que el robot es una herramienta útil para las enfermedades cardíacas. rehabilitación. De manera similar, se notó una percepción más positiva después de que los usuarios interactuaron con el robot. Además, este estudio de percepción permite potenciar el modelo social de interacción. en el futuro, con el objetivo de proporcionar una interacción más natural a través de funciones personalizadas, aumentando Habilidades sociales y compromiso de los usuarios durante la terapia.
Keywords: Robótica médica; Robotics in medicine; Rehabilitación médica; Medical rehabilitation; Tecnología médica; Medical technology; Interacción humano-robot; Human–robot interaction; Percepción; Perception; Robótica de asistencia social; Social assistive robotics; Compañero robótico; Robotic companion; UTAUTO modelo de aceptación; UTAUT acceptance model; Aceptación de tecnología; Technology acceptance; Rehabilitación cardiaca; Cardiac rehabilitation